Taiwan's Digital Public Diplomacy Towards Indonesia in Supporting its New Southbound Policy [Diplomasi Publik Digital Taiwan terhadap Indonesia dalam Mendukung Kebijakan Baru Arah Selatan] - Isnarti, Rika (Jurnal Politica, 2023)
This research aims to analyze Taiwan’s digital public diplomacy to Indonesia and generally in ASEAN countries in supporting Taiwan’s New Southbound Policy. It concerns elaborating and assessing to what extent digital diplomacy can assist Taiwan in achieving its new southbound policy goals and its limitations. This paper assesses Taiwan government’s social media, especially the Ministry of Foreign Affairs official social media and other digital media platforms that have been used to promote and inform New Southbound Policy and the president's social media accounts. It employs digital diplomacy in International Relations as a conceptual framework that is part of public diplomacy. This research is a qualitative content analysis, that analyzed terms such as New Southbound Policy, Indonesia, and Taiwan. The study found that Taiwan’s digital public diplomacy support its New Southbound Policy towards Indonesia in term of, but is not limited to, resource sharing, people-to-people exchange, and promoting institutional links. It meets digital diplomacy efficiency and objectives. Taiwan's digital diplomacy can achieve its agenda-setting and presence expansion but limited in generating optimal convensation. Those media platforms used in Taiwan’s digital diplomacy, can meet digital diplomacy objectives that are delivery of information, consular service, and engagement and expand the network.AbstrakPenelitian ini bertujuan untuk menganalisis diplomasi publik digital Taiwan di Indonesia dan umumnya di negara-negara ASEAN dalam mendukung Kebijakan Baru Arah Selatan Taiwan. Ini berkaitan untuk menguraikan dan menilai sejauh mana diplomasi digital dapat membantu Taiwan dalam mencapai tujuan Kebijakan Baru Arah Selatan dan keterbatasannya. Tulisan ini menilai media sosial pemerintah Taiwan, khususnya media sosial resmi Kementerian Luar Negeri dan platform media digital lainnya yang telah digunakan untuk mempromosikan dan menginformasikan Kebijakan Baru Arah Selatan dan akun media sosial presiden. Ini menggunakan diplomasi digital dalam Hubungan Internasional sebagai kerangka konseptual yang merupakan bagian dari diplomasi publik. Penelitian ini merupakan analisis konten kualitatif, yang menganalisis istilah-istilah seperti Kebijakan Baru Arah Selatan, Indonesia, dan Taiwan. Studi ini menemukan bahwa diplomasi publik digital Taiwan mendukung Kebijakan Baru Arah Selatan terhadap Indonesia dalam hal, tetapi tidak terbatas pada, pembagian sumber daya, pertukaran orang-ke-orang, dan mempromosikan hubungan kelembagaan. Ini memenuhi efisiensi dan tujuan diplomasi digital. Diplomasi digital Taiwan dapat mencapai penetapan agenda dan perluasan kehadirannya tetapi terbatas pada optimalisasi dalam menghasilkan percakapan. Platform media yang digunakan dalam diplomasi digital Taiwan tersebut, dapat memenuhi tujuan diplomasi digital yaitu penyampaian informasi, layanan konsuler, dan keterlibatan serta memperluas jaringan.